Division Made Easy - Wingard-Nelson, Rebecca; LaBaff, Tom (Berkeley Heights, NJ : Enslow Elementary, 2005)
Explains the mathematical process of division in simple terms, providing examples of the use of division in everyday life, as well as methods of doing long division, using powers of ten, and solving word problems.
Includes bibliographical references (p. 46-47) and index.
Keywords: Division